VEGF-B EXPRESSION AS A PREDICTIVE BIOMARKER FOR NEOADJUVANT CHEMOTHERAPY RESPONSE IN LOCALLY ADVANCED STAGE BREAST CANCER - Triyanto, Lopo; Hari, Mada (Mandala Of Health, 2025)
Background: Breast cancer is one of the most common malignancies in women. In Indonesia, most cases are diagnosed at an advanced stage, which makes therapy success more challenging. Neoadjuvant chemotherapy is a commonly used initial approach to shrink tumor size before surgical intervention. However, not all patients show a good response to this therapy. One important mechanism in cancer progression is angiogenesis, which is regulated by growth factors such as VEGF-B. VEGF-B plays a role in blood vessel formation and is associated with more aggressive tumor characteristics. Therefore, VEGF-B expression has the potential to be used as a predictive biomarker for chemotherapy response. Methods: This study used a prospective cross-sectional design involving 30 patients with locally advanced breast cancer at RSUP Dr. Hasan Sadikin, Bandung. All patients received three cycles of neoadjuvant chemotherapy with the CAF regimen (cyclophosphamide, doxorubicin, and 5-fluorouracil), followed by modified radical mastectomy. VEGF-B expression was assessed through immunohistochemical examination of biopsy samples. Chemotherapy response was evaluated based on clinical changes in tumor size and classified as complete response, partial response, or no response. Data analysis was performed using Spearman's test, chi-square, and multivariate logistic regression. Results: The average age of the patients was 47.9 years. Two patients (5%) showed a complete response, 20 patients (50%) had a partial response, and 18 patients (45%) did not respond. Most patients had high tumor grade (52.5%). Moderate VEGF-B expression was found in 60% of patients, and strong expression in 40%. There was a significant relationship between age (p = 0.023), tumor grade (p = 0.027), and VEGF-B immunoexpression (p = 0.026) with chemotherapy response. Logistic regression analysis showed that VEGF-B expression (OR = 0.16; 95% CI: 0.03–0.82) and age (OR = 3.33; 95% CI: 1.30–8.60) were significant predictors of therapy success. Conclusion: High VEGF-B expression is associated with a decreased response to neoadjuvant chemotherapy. In addition, younger age also showed a tendency toward a lower response. VEGF-B may be considered a potential predictive biomarker in the early evaluation of locally advanced breast cancer patients to improve therapy personalization and treatment effectiveness.